The Effect of Product Quality, Brand Image and Social Media Influencer on Purchase Decision of Scarlett Whitening Product on Social Media Instagram in DKI Jakarta - Yunita Pratiwi; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of product quality, brand image and social media influencers on purchasing decisions for Scarlett Whitening products on Instagram social media in DKI Jakarta. The research method used in this study uses a quantitative approach. The source of the data in this research is primary data which is distributed in the form of a questionnaire to 100 respondents of Scarlett Whitening consumers in DKI Jakarta. The sampling technique in this study used non-prabability sampling with purposive sampling. The data analysis technique used in this study is the Multiple Linear regression method and hypothesis testing which has been processed using the IBM SPSS Version 23 application to measure the regression coefficient. Based on the results of the partial t-test research found that product quality (X1) has a positive and significant effect on purchasing decisions, this can be seen from the results of the t-test where t count > t table (2.577 > 1.98498) and significant (0.011 < 0.05). Brand image (X2) has a positive and significant effect on purchasing decisions, this can be seen from the results of the t test where t count >t table (5.234 > 1.98498) and significant (0.000 < 0.05). And Social Media Influencer (X3) has a positive and significant effect on purchasing decisions, this can be seen from the results of the t test where t count > t table (7.600 > 1.98498) and significant (0.000 < 0.05). Therefore, it can be concluded that product quality, brand image and social media influencers have a positive and significant effect on purchasing decisions.